Study on the effects of microencapsulated Lactobacillus delbrueckii on the mouse intestinal flora. (3rd October 2015) - Sun, Qingshen; Shi, Yue; Wang, Fuying; Han, Dequan; Lei, Hong; Zhao, Yao; Sun, Quan
Abstract: Objective : To evaluate the protective effects of microencapsulation on Lactobacillus delbrueckii by random, parallel experimental design. Materials and methods : Lincomycin hydrochloride-induced intestinal malfunction mouse model was successfully established; then the L. delbrueckii microcapsule was given to the mouse. The clinical behaviour, number of intestinal flora, mucous IgA content in small intestine, IgG and IL-2 level in peripheral blood were monitored. The histological sections were also prepared. Results : The L. delbrueckii microcapsule could have more probiotic effects as indicated by higher bifidobacterium number in cecal contents. The sIgA content in microcapsule treated group was significantly higher than that in non-encapsulated L. delbrueckii treated group ( p  < 0.05). Intestine pathological damage of the L. delbrueckii microcapsule-treated group showed obvious restoration. Conclusion : The L. delbrueckii microcapsules could relieve the intestinal tissue pathological damage and play an important role in curing antibiotic-induced intestinal flora dysfunction.